KEBIASAAN BELAJAR SISWA DALAM MENGIKUTI MATA PELAJARAN KRIA TEKSTIL DENGAN TEKNIK BORDIR DI SMK NEGERI 8 PADANG - HANDAYANI, VIDIA; zahri, wildati; izwerni, izwerni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This research to exspress about student learning habbit in Kria Tekstillearning with bordir technic at vocational high school 8 of padang State, includlearning habit, faithful learning, reading the book, and follow the axams. Thisresearch is kuantitative research to description and interprestation about thestudent learning habbit. The sample is the student at X class, questioner with likertused to get data with percentase technic and the great level of responden. Theresult of the research indicate that learning habbit of student in Kria tekstillearning use Bordir technic at vocasional high school 8 of Padang state at goodchategory. Key Word: Learning Habbit, Faithful Learning, Reading The Book, and FollowThe Exams.